Implementation of Growth Mindset in Islamic Education and Its Impact on Character Development of Students at MTs. Muhammadiyah Pekanbaru - Baidarus, Baidarus; Fithri, Radhiyatul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the implementation of a growth mindset in Islamic education at Madrasah Tsanawiyah Muhammadiyah 1 and 2 Pekanbaru and its impact on character development among students. A qualitative descriptive approach was used in this research. Data collection techniques were conducted through in-depth interviews, observations, and document analysis. The results of the study indicate that the growth mindset is applied in teaching through the reinforcement of Islamic values that support the mental and emotional development of students. Positive impacts found include increased self-confidence, patience, perseverance, and reliance on Allah in facing academic and non-academic challenges. Additionally, there is an improvement in critical and creative thinking skills, which play a role in character development. Overall, the implementation of the growth mindset has proven to contribute significantly to the character development of students at Madrasah Tsanawiyah Muhammadiyah 1 and 2 Pekanbaru.